Pengaruh Karakteristik Pemerintah Daerah Terhadap Opini Audit - Firdaus, Muhammad Haikal (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the influence of local government characteristics on audit opinion. The sample in this study were 16 provinces in Indonesia. The data collection technique used purposive sampling with LKPD data from 2008 - 2018. This study used binomial logistic regression data analysis methods assisted by SPSS software. Based on the research results, it is known that the size of the region, the level of dependence of the regional government, the level of wealth of the local government, and the level of regional government spending have a positive and significant effect on the audit opinion. The simultaneous test shows that the variables of Regional Size, Level of Regional Government Dependence, Level of Regional Government Wealth, and Level of Regional Government Expenditures jointly affect the Audit Opinion. The Nagelkerke R2 value is 0.305, which means that the Regional Government Characteristics variable consisting of Regional Size, Local Government Dependency Level, Regional Government Wealth Level, and Local Government Expenditure Level can be explained by the independent variable, namely audit opinion of 30,5% while the remaining 69,5% explained by other variables outside the study.